Peran Viktimologi dalam Perlindungan Hak-Hak Korban Kejahatan di Indonesia - Ilham Beni Hamadi Harahap; Wahdaniah Sitorus (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2026)
Victimology, as a branch of criminology, plays a crucial role in understanding the position and needs of victims in a crime. This study aims to analyze the role of victimology in efforts to protect the rights of crime victims in Indonesia, particularly from the perspective of law and victim protection policies. The research method used is a normative legal research method with a regulatory and conceptual approach, through a review of various laws and regulations, scientific literature, and documents related to victim protection. The results show that victimology has made a significant contribution in shifting the paradigm of the criminal justice system from being more perpetrator-oriented to more victim-oriented. In the Indonesian context, victim protection has been accommodated through various regulations and institutions that play a role in providing victims' rights, such as the right to protection, restitution, recovery, and psychological recovery. However, the implementation of this protection still faces various challenges, including limited understanding among law enforcement officials, victims' lack of access to protection mechanisms, and minimal outreach regarding victims' rights. Therefore, strengthening the victimology perspective in the legal system and public policy is essential to achieve more comprehensive protection.